Suppression of group delay dispersion oscillations of highly dispersive mirrors by non-uniformity and post-deposition treatment. (October 2021) - Chen, Yu; Hahner, Daniel; Trubetskov, Michael; Pervak, Vladimir
Highlights: Highly dispersive mirrors are designed, fabricated and characterized. Group delay dispersion oscillations are suppressed by a new post-deposition method. A shorter pulse with smaller pre-and post-pulses is obtained by this method. Abstract: A new method which employs two mirrors produced in one coating run with anti-phase group delay dispersion (GDD) is proposed to suppress GDD oscillations. The anti-phase GDD is realized by the spectral shift between the two mirrors caused by the non-uniformity and post-deposition annealing, for the first time to the best of our knowledge. The group delay (GD) and GDD oscillations are significantly suppressed by the two anti-phase GDD mirrors. Pulse analysis proves that the pulse quality can be improved after applying the new method. The pulses become shorter and have smaller pre- and post-pulses.